“Ready-to-use” two-week home exercise program targeting depressive symptoms: pilot study - Sandra, Dasha A.; Olson, Jay A.; Pageaux, Benjamin; Roy, Mathieu (Frontiers in Psychiatry, 2023)
Exercise is an evidence-based treatment for depressive symptoms, yet it often requires specialised knowledge and equipment, or professional supervision. Lay people in certain contexts, for example in remote locations or under pandemic restrictions, often lack these resources and thus cannot use exercise to manage their depressive symptoms. We developed a two-week home exercise program that bypasses these barriers and tested it in university students during pandemic restrictions. In an online study we recruited 490 participants to complete a week of baseline symptom monitoring then follow the exercise program for two weeks (6 sessions) at home. The exercise program involved aerobic and resistance training; each session lasted approximately 45 minutes. After two weeks of following the intervention, participants reported lower depressive (standardised β = -0.71 [-1.05, -0.38]-0.78 [-1.14, -0.41]) and anxiety (β = -0.87 [-1.19, -0.55]-0.83 [-1.15, -0.51]) symptoms.; Tthe effects were similar to those from longer-term professionally supervised exercise interventions (albeit ones compared to a control group). Compliance with the program was high, with participants completing 80% [67.3, 92.7] of the exercises. Although we cannot make causal conclusions, our results suggest that the brief home exercise program may have potential to reduce depressive symptoms in young adults.